The Use of the Adaptation Potential Reduction Model for Reproductive Toxicity Research In Vivo. (21st November 2020) - Tyshko, Nadezhda V.; Sadykova, Elvira O.; Shestakova, Svetlana I.; Nikitin, Nikolay S.; Trebukh, Marina D.; Loginova, Maria S.; Pashorina, Valentina A.; Zhminchenko, Valentin M.
Abstract : The modeling of adaptation potential decrease in rats due to modification of the diet's vitamin–mineral composition allows to increase animals' sensitivity to toxic load in reprotoxicological experiments. The threshold values of vitamins B1, B2, B3, and B6 and mineral substances Fe 3+ and Mg 2+ in the diet, which lead to a considerable reduction of laboratory animals' adaptation potential, have been determined as 19% (from the basic level in the diet) for males and 18% for females. The efficiency of this model has been confirmed in a reprotoxicological experiment with glyphosate as a toxic factor: the action of the toxic factor against the background of reduced availability of B vitamins and salts Fe 3+ and Mg 2+ led to significant changes in such indicators of reproductive function as mating efficiency, postimplantation loss, and the total number of alive pups, while the toxic effect of glyphosate was not so pronounced against the normal level of essential substances. The obtained results prove that this adaptation potential reduction model can be recommended for the research of the low-toxicity objects reproductive toxicity in rats and for the safety assessment of novel food, in particular.